A comparative study on partially purified amylase isozymes from three carp species - Ctenopharyngodon idella, Cirrhinus mrigala and Hypselobarbus pulchellus - Narasimhan, Sridhar; Rajagopalan, Anusha; Umalatha (Indian Journal of Fisheries, 2025)
Effective utilisation of starch from feeds by herbivorous fishes depends on the competency of amylases in their system. In this study, a comparative account of partial purification of α-amylases from economically important carp species such as grass carp (Ctenopharyngodon idella), mrigal (Cirrhinus mrigala) and Hypselobarbus pulchellus along with their characterisation has been evaluated to understand the nature of the enzyme and its isozymes with their molecular weight. The analysis of partially purified enzyme (PPE) revealed the presence of three ( 64, 54 and 52.5 kDa), two ( 65.5 and 55 kDa) and six ( 79, 78, 66, 58, 49 and 43 kDa) isozymes for grass carp, mrigal and pulchellus respectively with optimum pH ranging between 4.5-7.5 and optimum temperature between 25-55°C. Amylases of three fishes were characterised to be metalloenzymes with serine and thiol groups at their active site. Keywords: Characterisation, Herbivores, Isoenzymes